1996
DOI: 10.1016/0014-5793(96)00432-2
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum neurotoxin light chains inhibit both Ca2+‐induced and GTP analogue‐induced catecholamine release from permeabilised adrenal chromaffin cells

Abstract: Using digitonin-permeabilised bovine adrenal chromaffin cells, the effects of botulinum neurotoxin light chains on exocytosis triggered by Ca 2+ or by GppNHp were examined. Botulinum neurotoxin D light chain, prepared as a His6-tagged recombinant protein, cleaved VAMP and substantially inhibited catecholamine release due to Ca 2+ and GppNHp. Botulinum neurotoxin C1 and E light chains produced partial inhibition of both Ca 2+-and GppNHp-induced catecholamine release. These results suggest that Ca2+-dependent ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 51 publications
(65 reference statements)
1
13
0
Order By: Relevance
“…However, this complex is not essential per se in the triggered fusion steps of exocytosis because in our work higher [Ca 2+ ]free overcame the block to fusion (seen at 'physiological' [Ca 2+ ]free) caused by proteolysis. Such recovery has also been documented in earlier experiments with Clostridial toxins (Dreyer and Schmitt, 1983;Ahnert-Hilger and Weller, 1993;Bittner and Holz, 1993;Lawrence et al, 1994;Glenn and Burgoyne, 1996;Lawrence et al, 1996;Capogna et al, 1997;Land et al, 1997;Fassio et al, 1999), suggesting that the concept of a regulatory complex may extend beyond the present system. In general, the testing and rescue of exocytosis at only one [Ca 2+ ]free after complex disruption tells us a great deal about the modulatory role of the complex.…”
Section: Snares and The Process Of Exocytosissupporting
confidence: 75%
“…However, this complex is not essential per se in the triggered fusion steps of exocytosis because in our work higher [Ca 2+ ]free overcame the block to fusion (seen at 'physiological' [Ca 2+ ]free) caused by proteolysis. Such recovery has also been documented in earlier experiments with Clostridial toxins (Dreyer and Schmitt, 1983;Ahnert-Hilger and Weller, 1993;Bittner and Holz, 1993;Lawrence et al, 1994;Glenn and Burgoyne, 1996;Lawrence et al, 1996;Capogna et al, 1997;Land et al, 1997;Fassio et al, 1999), suggesting that the concept of a regulatory complex may extend beyond the present system. In general, the testing and rescue of exocytosis at only one [Ca 2+ ]free after complex disruption tells us a great deal about the modulatory role of the complex.…”
Section: Snares and The Process Of Exocytosissupporting
confidence: 75%
“…5, 6), which until now has been understood poorly. One fact that we and others knew is that these two forms of exocytosis are both SNAREdependent (Banerjee et al, 1996;Glenn and Burgoyne, 1996;Wang et al, 2004). Whereas Martin and coworkers found that cytosolic proteins including phosphatidylcholine transfer protein (Hay and Martin, 1993), phosphatidylinositol phosphate kinases (Hay and Martin, 1993;Aikawa and Martin, 2003; and CAPS (Ca 2ϩ -dependent activator protein for secretion) (Walent et al, 1992) are critical for Ca 2ϩ -dependent exocytosis, they also found that these proteins are dispensable for GTP-dependent exocytosis (Klenchin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The same SNAREs are involved in the exocytosis of chromaffin granules (Glenn and Burgoyne, 1996) and secretory granules in PC12 cells (Banerjee et al, 1996). Furthermore, it is known that ϳ 20% of both syntaxin 1 and SNAP-25 are present on vesicles, although the majority are localized to the plasma membrane (Tagaya et al, 1995;Walch-Solinema et al, 1995;Gaisano et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The same SNAREs also have been found to be involved in exocytosis of chromaffin granules (Glenn and Burgoyne, 1996) and secretory granules in PC12 cells (Banerjee et al, 1996). Because secretory granules derive from ISGs, we asked whether any of the SNAREs involved in exocytosis are also involved in ISG-ISG fusion.…”
Section: Neurotoxin Cleavage Of Syntaxin 1 and Vamp2 Does Not Inhibitmentioning
confidence: 99%